Isolation, characterization, and hepatoprotective properties of betulinic acid and ricinine from Tetracarpidium conophorum seeds (Euphorbiaceae). Issue 3 (11th June 2020) - Oriakhi, Kelly; Uadia, Patrick O.; Shaheen, Farzana; Jahan, Humera; Ibeji, Collins U.; Iqbal, Choudhary M.
Abstract: The present study is to isolate and characterize betulinic acid and ricinine from T. conophorum seeds. Phytochemical investigation on hexane fraction of T. conophorum seeds led to the isolation of two compounds, Betulinic acid (1 ), and Ricinine (2 ). Betulinic acid and ricinine were screened against HepG2 cells and tested in vivo in CCl4 ‐induced experimental rats model. Results from this study showed that the compounds had hepatoprotective and cytotoxic activities. It was observed that betulinic acid inhibited HepG2 cell with percentage inhibition of 54% compared with standard doxorubicin (64%), while ricinine was inactive against HepG2 cell lines. Furthermore, molecular docking was carried out on betulinic acids and ricinine, with binding energies of −11.2 kcal/mol and –5.4 kcal/mol, respectively, indicating strong binding sites and interactions with Hepatitis B Virus DNA polymerase. Therefore, findings from this study suggest that betulinic acid possess cytotoxic and hepatoprotective properties, while ricinine exhibited hepatoprotection in CCl4 ‐induced liver damage. Practical applications: Medicinal plants contain unrestricted ability to make compounds that intrigue researchers in the quest for novel phyto‐therapeutic drugs. The continuous exploration of new compounds in the medicinal plant is an auspicious strategy for the prevention of diseases. Therefore, the purpose of this research is to evaluate the cytotoxic and hepatoprotective compounds (betulinic acid and ricinine) isolated from T. conophorum seeds. Abstract : The present study show that betulinic acid isolated from T. conophorum seeds possess anti‐proliferative activity against human hepatocarcinoma cells and hepatoprotective activities against CCl4 ‐induced hepatotoxicity, while ricinine exhibited hepatoprotective potential in CCl4 rat model in vivo. It was also observed that betulinic acid and ricinine possess strong affinity and better interaction in the active sites of Hepatitis B Virus DNA polymerase